Metode Takhrij Al-Hadis - N, Nurbaya; T, Tasbih; z, Zaenab (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Hadith is everything that originates from the Prophet Muhammad (peace be upon him), whether in terms of what was reported, conveyed through his words or sayings, decrees, interpretations, deeds, and so on. The emergence of hadith interpretations was due to the development of other disciplines, such as fiqh, tafsir, and history, which made it difficult for scholars to trace the sources of the hadith they cited. Initially, scholars had such extensive memorization of hadith that they did not need interpretations. However, as time passed and knowledge advanced, this extensive memorization began to weaken, leading to the need to trace hadith in hadith books. Several scholars have conducted takhrij studies on books circulating in society where the books do not explain the quality of the hadith included, sometimes this continues until now, even takhrij hadith then become integral to the process of interpreting a work, both previously published and newly published classical scholarly works. The aim of mentakhrij hadith is to find out the original source of a hadith, to be able to add to the treasury of hadith sanad, to be able to know the quality of a hadith and also to be able to clarify hadith law. With takhrij hadith requires steps in mentakhrij hadith by tracing and determining the text of the hadith and keywords in the hadith then carrying out an analysis process of the hadith and hadith books using either the lafaz matan, maudhu'i method or the sanad method then determining the source of the hadith books and evaluating them. degree so as to conclude the results of the hadith mentahrij in a systematic and critical way towards the hadith text and its translation, the source of the hadith, the degree of the hadith and so on.